Peningkatan Pemahaman Pencegahan Penyakit Patek (Antraknosa) Pada Tanaman Cabai di Desa Senggowar Kabupaten Nganjuk - M. Maulana Asegaf; Mochammad Ilyas Junjunan; M. Alfan Nashrullah; Ali Ridho Syafi'i; Ghina Mufidah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Currently Senggowar Village is entering the dry season, where most of the farmers here grow chili as a very profitable commodity. As one of the Work Projects from the Real Work Lecture (KKN) carried out in Senggowar village, Nganjuk regency. In determining and analyzing the problems that occur, you use the PAR method (Participatory Action Research) which involves the participation of resource persons and the surrounding community as data sources. The problem found in the field is that just before harvest time, chili plants should be able to produce superior chili products, but they are attacked by Patek disease (anthracnose) which makes chili plants less productive, which causes farmers to lose money. The activity carried out was counseling about preventing Patek disease (anthracnose) in chili plants, this activity aimed to provide knowledge about Patek disease and how to prevent it, so that losses caused by Patek disease do not recur. The purpose of this outreach is that farmers can know about how to prevent Patek disease in chili plants and be able to actualize it when entering the planting season.